Dreipassen – en magisk genstand? - Margrethe Hornstrup, Karen (Kuml, 2015)
The trefoil – a magical object? In 1997, a trefoil was found in a cremation pit at Bilstrup near Skive in Viborg county. The other grave goods, comprising fragments of arm rings and smaller rings, the stem of an iron pin, a small handled vessel etc., gave no hint as to the trefoil’s function and I have therefore searched ever since for information on these small ornaments (figs. 1 and 3). Trefoils are relatively rare finds, but are known from across most of Denmark (fig. 2 and catalogue) and large parts of Europe: Norway, Germany, Slovenia, Hungary, France and Italy, as well as possibly Serbia and Greece. They were also around for a remarkably long period of time, from c. 900 to c. 400 BC. As the trefoil has never been subjected to an independent study and analysis, but only described and discussed in minor notes, I will investigate here how it was used and the functions it had, based on finds from various European areas. A trefoil consists of three rings soldered together to form a triangle, but a few examples are cast in one piece. Its size varies from c. 2.5 to 5 cm. There are some special versions, for example where the rings are joined together by short bars, but these are not included here. In Germany and a few other countries the trefoil is referred to as the Dreipass, but in Denmark these objects have been recorded under various different names and are therefore difficult to trace in the archives. Trefoils are usually made of bronze, but there are some versions carved in sandstone or even made from human skulls. They tend to be found in graves, but are also recorded from hoards. In Denmark, they fall within a dating range extending from Bronze Age period V up to and including Pre-Roman Iron Age period I. The Scandinavian finds are presented in figure 2 and in the catalogue. As can be seen from these, the trefoil has been recorded from a number of graves, but has also been found in two hoards – at Voldtofte in Funen and Falling in eastern Jutland. Trefoils were presumably produced locally, as an example has been found in a pit together with casting waste at Otterup on Funen (cat. no. 11). With the aim of determining the trefoil’s function, an analysis was first carried out relating it to gender. An examination of finds combinations from Scandinavia shows that the trefoil occurs exclusively in graves containing ornaments such as neck and arm rings (table 1). It is possible that a few of these could be child graves, as suggested for example by the oath ring from the grave at Gåsdal, which has an internal diameter of only c. 5 cm (fig. 4). The other graves are in Germany, France and Italy (table 2). Even though the trefoil occurs in a large number of German graves, it is combined with other finds in only three cases, and in only one of these is a female ornament involved, i.e. an arm ring. As one of the other graves contains a knife, together with two twisted rings and two accessory vessels, this could be the grave of a man (table 2). Two of the graves in France have both neck and arm rings, whereas the third merely contains perforated animal teeth and a ceramic bead. France is also where the trefoils carved from human skulls were found, but there is unfortunately no information on their context. Two of these bone trefoils are now in the Corel Collection at the British Museum; one of them is illustrated in figure 5, together with a rounded disc perforated by three holes. The second example was apparently found together with two blue glass beads. Finally, mention should be made of a third example where the trefoil was attached to a necklace (fig. 6). Examination of the Italian graves, several of which contain particularly rich grave goods, reveals that three of these differ from the others by containing more than one trefoil (table 2). However, only grave 31 also has neck and arm rings. The grave at Padova can be interpreted as that of a man, because it contains an iron axe and an ornamented belt of sheet bronze. The other two graves contain glass beads and, according to Ludwig Pauli, these are characteristic of female and child graves. The result of the analysis is, accordingly, that trefoils are found primarily together with grave goods characteristic of women and possibly also children. The next question relates to how the trefoil was worn, and stray finds and finds from hoards are also included in this analysis. In one of the Italian graves, the trefoil is a pendant on a fibula and two metal chains are attached to one of its rings (fig. 7). A trefoil from Bömitz in Pomerania is fitted with a small eye, thereby confirming its use as a pendant. A necklace from the Voldtofte hoard on Funen incorporates several rings and a trefoil in a small spiral, and the same arrangement is seen on a neck ring from Juvigny, where the trefoil is made of human skull (figs. 8 and 6). In one of the Danish finds, the trefoil hangs from a long string of organic material (cat. no. 13). As metal neck rings are rare finds in graves, this was perhaps the usual way in which the trefoil was worn. It must be concluded that the trefoil was a form of ornament, more precisely a pendant, and there are several examples showing that it was worn suspended on neck rings of either metal or organic material, or alternatively attached to a fibula. Considering that the trefoil was in existence for about 500 years and was the only ornament that survived the extensive societal changes that took place in the period c. 800-400 BC, it presumably had great symbolic significance. It was, however, rare as an iconographic motif as it has only been found in this form on one artefact: a razor from Fousing, western Jutland (fig. 9). Due to its distribution as a plastic ornament and its association with female and possibly also child graves, it is presumed that the trefoil functioned as an amulet. Amulets are generally understood as being small objects that are worn on the body and which protect the individual wearing them from supernatural forces, misfortune and illness, as well as ensuring the successful delivery of children. They can also have curative powers if worn on the affected part of the body. In Central Europe in the Late Bronze Age and Early Iron Age, a variety of amulets emerged that existed for a long period of time: wheels, waterfowl, jingle plates and trefoils. Classical sources reveal that a number of small objects, such as corals, amber, perforated animal teeth, glass beads and so on, were also perceived as amulets at this time. The most significant analysis of amulets has been carried out by Ludwig Pauli on the basis of a large number of finds from graves in Central Europe, dating from the period relevant here. Pauli classifies a range of objects that cannot be considered as either ornaments, weapons or tools into five categories: a. noise-generating objects such as ceramic rattles and jingle plates, b. externally sensuous objects, such as human and animal figures, and less readily recognisable objects, such as trefoils, c. unfinished objects, casting waste and bent objects, d. abnormal or curious objects such as scrap metal, e. natural materials such as stone, amber, animal teeth, but also glass beads. His classification shows that these objects occur primarily in the graves of women and children, which corresponds to the use of trefoils in Scandinavia. It must therefore be concluded that the trefoil was most probably an amulet, regardless of whether it was made of bronze or of human skull, as there are several examples clearly showing its use as a pendant. The trefoil was a relatively rare artefact and its presence in the, by Scandinavian standards, richly-furnished Bilstrup grave and in elite graves in Central Europe shows that it possessed several layers of significance. Consequently, it was not merely a magical object but presumably also possessed symbolic importance, at the same time as being an ornament reserved for individuals from the uppermost strata of society. According to Ludwig Pauli, the use of amulets increased in periods of political and economic unrest, for example around 500 BC, and in Scandinavia there were violent societal upheavals from c. 800-400 BC. However, despite the many changes that took place during this period, the tradition of wearing this specific type of amulet prevailed across large parts of Europe. Karen Margrethe Hornstrup Moesgaard Museum